MARINE CURRENT ENERGY RESOURCE ASSESSMENT IN MALAYSIA - Kesavadasan, Thasaini Nambiar (Universiti Teknologi PETRONAS, 2020)
For electricity generation Malaysia is heavily based on fossil fuel. Despite its power supply steadily diminishing and the highly harmful environmental impact of fossil energy, the government has started to utilize biofuel and solar radiation to produce electricity. However, in Malaysia, the potential to harness other renewable sources, particularly ocean energy, has not been fully realised though other countries like France, Scotland and Korea has successfully extracted energy from ocean. This paper outlines the study of marine current energy a type of renewable energy which is obtained from offshore renewable energy which globally are moving into harnessing renewable energy to replace fossil fuel such as oil and gas. The aim of using the new energy sources is to ensure the country has safe and stable energy supply available.